Avances y discusiones sobre el uso de inteligencia artificial (IA) en educación - Tramallino, Carolina Paola (2024)
The aim of this research is to analyze scientific articles about artificial intelligence (AI) in an educational context. These articles were located using Google Scholar and Science Direct and were written in Portuguese, English, and Spanish from 2021 onwards. In 2022, ChatGPT was launched, a technology that is part of the concept called generative AI, created by machine learning techniques. This type of tool, which has been the subject of many discussions, has also gained traction in educational institutions. As a result, governments in many countries, concerned about AI’s impacts, are attempting to regulate its use. Among these articles, studies about AI literacy, the training of teaching staff, the need to address the topic in an interdisciplinary manner, and starting from elementary school, stand out.